Penerapan Social Network Analysis Dalam Menganalisis Kerjasama Tokopedia Dengan Boyband Korea BTS - Ignatius Adrian Mastan; Christianto Christianto (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
Tokopedia is an Indonesian technology company with a mission to achieve digitaleconomic equity. Since its founding in 2009, Tokopedia has transformed into aninfluential unicorn not only in Indonesia but also in Southeast Asia. On October 7,2019, Tokopedia announced a South Korean music group, BTS, to become the new brand ambassador for Tokopedia. BTS is a global mega star group from South Korea which is shaded by Big Hit Entertainment. Consisting of seven members including RM, Jin, SUGA, j-hope, Jimin, V, and Jung Kook, BTS was founded in 2013 and has had worldwide success. The extraordinary growth and achievements achieved by BTS have managed to break records in recent years so that BTS is designated as the persona of the Tokopedia brand. Through this collaboration, the public and BTS fans are expected to be closer to their inspirational figure. The various types of marketing currently carried out by Tokopedia in collaboration and collaboration with BTS have had a lot of impact on Tokopedia's sales. One of the marketing efforts that has been done by Tokopedia is using Twitter. Twitter is one of the social media used to attract consumers to buy products sold on Tokopedia. Using Social Network Analysis (SNA) provides a statistical tool for examining relational data not only on the characteristic attributes of individual actors, and focuses on explaining the patterns of relationships between actors, and analyzing the structure of these patterns. Social etwork representation is expressed in graph form because graph is the most fundamental type of social network representation. Social Network Analysis (SNA) argues that the relationship between nodes is important. The focus of Social Network Analysis (SNA) is on knowing the actors/nodes involved and how relationships occur. This study uses Social Network Analysis (SNA) to produce a structure of relationship data patterns between the collaboration between Tokopedia and Korean Boyband BTS which can help Tokopedia to review the collaboration that has been done. Tokopedia can take action in collaborating with BTS, to continuing or stopping or replacing with newbrand ambassadors.